Tinjauan Yuridis Penyelesaian Sengketa Tanah WarisYang Telah Terjadi Peralihan Hak Atas Dasar Jual Beli(Studi Putusan No. 129/Pdt.G/2015/Pn Skh Di Pengadilan Negeri Sukoharjo) - Putra, Adhinda Harrydiant, Shalman Al Farizi, S.H., S.E., M.M., M.Kn (2017)
Inheritance is a specified acquiring rights a plot of land, and because the object is one main element of the very self of the object. The heir will automatically obtain heir inheritance, if the heir does have the possession as it proved by valid documents. Hence, basically, if one considers he has the right to a home, then he must be able to prove legitimate title over a plot of land. However, if someone who considers he has the right to a land, but he is not able to prove the legitimate title, then he is not entitled to have complete control over that a plot of land. This research uses descriptive normative method, with primary and secondary data. Data collection techniques using literature studies, field studies. They are collected through the study of literature, field, by using qualitative data analysis.